Health Professionals' COVID-19 Vaccine Acceptance and Associated Factors in Tertiary Hospitals of South-West Ethiopia: A Multi-Center Cross- Sectional Study - Bekele Boche B.Pharm, MSc; Oliyad Kebede B.Pharm, MSc; Mekonnen Damessa B.Pharm, MSc; Tadesse Gudeta B.Pharm, MSc; Diriba Wakjira Bsc. Midwifery, MSc (SAGE Publishing, 2022)
Background Acceptance of the COVID-19 vaccine by health professionals highly influences the communities' decision to receive the vaccine, because health professionals are perceived to be a reliable source of health information. Hence, this study aimed at assessing COVID-19 vaccine acceptance and associated factors among health professionals in two tertiary hospitals in southwest Ethiopia. Methods A cross-sectional study was conducted among 319 health professionals working in Jimma University Medical Center and Mizan-Tepi university teaching hospital, southwest Ethiopia, from June 30, 2021 to July 30, 2021. Data were collected by a structured self-administered questionnaire and analyzed by SPSS version 23. A multivariate logistic regression model was used to identify independent factors associated with health professionals' covid-19 vaccine acceptance. Variables with P -value < .25 on univariate analysis were candidates for multivariate logistic regression. Then, variables with P -value < .05 at 95% CI in multivariate logistics regression were considered statistically significant. Results Of the total participants, 232 (72.73%) received COVID-19 vaccines. Among non-vaccinated health care professionals, 82 (94.3%) of them stated, worries about the safety and side effects of the vaccines, as the reason for non-acceptance. Factors such as, friends or families diagnosed with COVID-19 (AOR = .086; CI: 95%, .041-.18; P = .001), and attitudes and beliefs about COVID-19 and its vaccine (AOR = .129; CI: 95%, .037-.449; P = .001), were significantly associated with the acceptance of COVID-19 vaccine. Conclusion More than one-fourth of health professionals who did not accept COVID-19 vaccines require immediate intervention through awareness creation on the safety and adverse effects of the vaccine by the government and other stakeholders. Otherwise, the community may in large reject the vaccine as they trust health professionals.